Emotional Implication: Performing Within Emotional Gaps - Kristie S. Fleckenstein (Journal of the Assembly for Expanded Perspectives on Learning, 1995)
The role of emotional implication is a process by which writers leave and fill emotional gaps within a text, thus creating their readers, text worlds, and themselves.